A New Hybrid Lead‐Free Metal Halide Piezoelectric for Energy Harvesting and Human Motion Sensing - Guo, Tian‐Meng; Gong, Yong‐Ji; Li, Zhi‐Gang; Liu, Yi‐Ming; Li, Wei; Li, Zhao‐Yang; Bu, Xian‐He (Small (Weinheim an der Bergstrasse, Germany), 2022)
Hybrid organic–inorganic piezoelectrics have attracted attention due to their simple synthesis, mechanical flexibility, and designability, which have promising application potential in flexible sensing and self‐powered energy harvesting devices. Although some hybrid piezoelectrics are discovered, most of their structures are limited by the perovskite‐type and often contain lead. Herein, the synthesis, structure, and piezoelectric properties of a new hybrid lead‐free metal halide, (BTMA)2CoBr4 (BTMA = benzyltrimethylammonium) are reported. The experimental and theoretical results demonstrate that this material simply composed of [CoBr4]2− tetrahedra and BTMA+ cations exhibits significant piezoelectricity (d22 = 5.14, d25 = 12.40 pC N−1), low Young's and shear moduli (4.11–17.56 GPa; 1.86–7.91 GPa). Moreover, the (BTMA)2CoBr4/PDMS (PDMS = polydimethylsiloxane) composite thin films are fabricated and optimized. The 10% (BTMA)2CoBr4/PDMS‐based flexible devices show attractive performance in energy harvesting with an open‐circuit voltage of 19.70 V, short‐circuit current of 4.24 µA, and powder density of 11.72 µW cm−2, catching up with those of piezoelectric ceramic composites. Meanwhile, these film devices show excellent capability in accurately sensing human body motions, such as finger bending and tapping. This work demonstrates that (BTMA)2CoBr4 and related piezoelectric lead‐free halides can be promising molecular materials in modern energy and sensing applications. A hybrid lead‐free metal halide, (BTMA)2CoBr4 (BTMA, benzyltrimethylammonium), is demonstrated to exhibit significant piezoelectricity and soft elastic properties. Moreover, (BTMA)2CoBr4‐based composite films are fabricated for energy harvesting and human body motion sensing with attractive performance. This work broadens the landscape of molecular piezoelectric materials by paying more attention to the non‐perovskite‐type and lead‐free hybrid organic‐inorganic systems.